Codes of Practice for Geotechnical Engineering: Site Investigations ( SI ): Review Paper (Journal of Building and Road Research, 2021)
This paper presents a review of some national and regional codes of practice in the area of Geotechnical engineering siteinvestigation (SI). The goal is to identify some significant issues relevant to professional practice in Sudan and to highlight howthey were approached and dealt with in different codes.The scope of the SI comprises the number of points to be investigated. these may be test pits, boreholes, fieldsoundings, geophysical soundings. The extent of the SI is generally described by the depth of boreholes and /or typesof field soundings. The scope and extent of SI are strongly related to the types of structures and loadings as well as to thegeotechnical character of the site.The final result of the SI is presented in a geotechnical report, including field work, laboratory work and recommendationsfor design and construction. The report must be prepared by an experienced Geotechnical Engineer.The fact that SI is usually carried out in the very early stages of the project, when even the project funding may not havebeen fully secured, tends to create a situation where costs available for SI may be restricted. It is widely believed that SI isa very significant component of any civil engineering project. While the cost of the SI is a minor component, it is of majorimportance to project risk management and will positively affect total costs. It is recommended that a Sudanese Code of Practice for Geotechnical Engineering be adopted to regulate and upgradethe professional practice in this area. This activity should be carried out under the auspices of the national Standardsorganization. The Sudanese Society of Soil Mechanics and Geotechnical Engineering can be instrumental in theseactivities.
Keywords: Geotechnical Engineering; Site Investigations